Gerechtigkeit und deren intertextuelle und intermediale Beziehungen im Werk des Magisters Vincentius - Bering , Piotr (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The aim of present paper is a closer analyze of some textual construction which are imitating a legal action at court. The scene of imagined court were popular in medieval dramaturgy, they are often used as a plot for scenic action. A particular case was created by Master Vincentius (12th Cent.): a passage from chronicle which presents a possible staging of court action.